2009
DOI: 10.4049/jimmunol.0900228
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Increases Allergic Airway Inflammation

Abstract: The prevalence of allergies and asthma among the world’s population has been steadily increasing due to environmental factors. It has been described that exposure to ozone, diesel exhaust particles, or tobacco smoke exacerbates allergic inflammation in the lungs. These environmental oxidants increase the levels of cellular reactive oxygen species (ROS) and induce mitochondrial dysfunction in the airway epithelium. In this study, we investigated the involvement of preexisting mitochondrial dysfunction in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
185
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(192 citation statements)
references
References 75 publications
6
185
0
Order By: Relevance
“…This compound can then reach the cytoplasm after opening of the mitochondrial transition pore (refs. 69-71); thereby, hydrogen peroxide generated in mitochondria acts as a signaling mediator that induces NF-κB activation (12,72). Our data are in support of these studies, as we found that epithelial Mt-CaMKIIN expression reduced stimulant-mediated oxidative stress and altered mitochondrial function (measured by Mt-ROS and OCR), which correlated with reduced NF-κB activation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This compound can then reach the cytoplasm after opening of the mitochondrial transition pore (refs. 69-71); thereby, hydrogen peroxide generated in mitochondria acts as a signaling mediator that induces NF-κB activation (12,72). Our data are in support of these studies, as we found that epithelial Mt-CaMKIIN expression reduced stimulant-mediated oxidative stress and altered mitochondrial function (measured by Mt-ROS and OCR), which correlated with reduced NF-κB activation.…”
Section: Discussionsupporting
confidence: 80%
“…in asthma; however, sources of these phenomena are unclear (6,7,(10)(11)(12)54). One potential clue is that mitochondrial CaMKII inhibition is protective in a variety of myocardial injury models linked to elevated ROS and mitochondrial dysfunction (7,20,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial form of SOD (MnSOD or SOD2) is oxidatively inactivated in asthmatic airway samples 4 , suggesting that impairment of mitochondrial oxidative defenses might contribute to the asthmatic phenotype. Evidence for mitochondrial injury in murine asthma models 2,3 , discussed earlier, is consistent with this hypothesis, though the mechanism(s) of mitochondrial damage have not been elucidated. SOD2 polymorphisms are also associated with bronchial hyperresponsivenss in humans 83 .…”
Section: Glutathione Modulating Reagentssupporting
confidence: 67%
“…To mimic oxidative stress conditions we treated the cells with antimycin A, which binds to cytochrome b and inhibits electron flow from semiquinone to ubiquinone, consequently increasing the steady state concentration of semiquinone and resulting in electron escape from complex III [43,44]. This impairment of the electron transport system can increase mitochondrial ROS generation leading to oxidative damage of mtDNA [45].…”
Section: Discussionmentioning
confidence: 99%